Association of preoperative body mass index with postoperative complications and survival for patients with gastric cancer: A systematic review and meta-analysis. - Zhenzhen Li; Lili Cui; Jing Sun; Wanlu Liu (PLoS ONE)
Objective The relationship among body mass index (BMI), postoperative complications, and clinical outcomes in patients undergoing gastrectomy for gastric cancer remains unclear. This study aimed to evaluate this association using a meta-analysis. Method We conducted a systematic search of the PubMed, Embase, and Cochrane Library databases up to February 25, 2024. Patients were classified into underweight (<18.5 kg/m2), normal weight (18.5-25.0 kg/m2), and overweight (≥25.0 kg/m2) groups based on BMI categories. Meta-analysis was performed using a random-effects model. Additionally, exploratory sensitivity and subgroup analyses were performed. Results Twenty-two studies involving 41,144 patients with gastric cancer were included for quantitative analysis. Preoperative underweight (odds ratio [OR]: 1.26; 95% confidence interval [CI]: 1.03-1.55; P = 0.024) and overweight (OR: 1.19; 95%CI: 1.09-1.30; P <0.001) were associated with an increased risk of postoperative complications. Furthermore, preoperative underweight was associated with poorer overall survival (hazard ratio [HR]: 1.40; 95%CI: 1.28-1.53; P <0.001), whereas preoperative overweight was associated with better over-survival (HR: 0.82; 95%CI: 0.73-0.91; P <0.001). Furthermore, preoperative underweight was not associated with disease-free survival (HR: 1.48; 95%CI: 0.97-2.26; P = 0.069), whereas preoperative overweight was associated with longer disease-free survival (HR: 0.80; 95%CI: 0.70-0.91; P = 0.001). In terms of specific postoperative complications, preoperative underweight was associated with an increased risk of septic shock (OR: 3.40; 95%CI: 1.26-9.17; P = 0.015) and a reduced risk of fever (OR: 0.39; 95%CI: 0.18-0.83; P = 0.014). Preoperative overweight was associated with an increased risk of wound infections (OR: 1.78; 95%CI: 1.08-2.93; P = 0.023), intestinal fistula (OR: 5.23; 95%CI: 1.93-14.21; P = 0.001), arrhythmia (OR: 6.38; 95%CI: 1.70-24.01; P = 0.006), and pancreatic fistula (OR: 3.37; 95%CI: 1.14-9.96; P = 0.028). Conclusion This study revealed that both preoperative underweight and overweight status were associated with an increased risk of postoperative complications. Moreover, the postoperative survival outcomes were significantly better in overweight compared to that of underweight patients. Trial registration Registration: INPLASY202480004.